Aesthetic and Non-aesthetic Indications for Orbicularis Oculi Myectomy - Viterbo, Fausto [UNESP]; Joethy, Janna; Brock, Ryane Schmidt (Springer Nature, 2016)
Introduction: Crows’ feet wrinkles are caused by the action of the orbicularis oculi muscle on overlying skin. Treatment options range from botulinum toxin to a multitude of surgical methods. We first described our technique in 2003 and refined it in 2006. We highlight the evolution of our technique and look at our results to assess the effectiveness of our technique. Objective: The aim of this article is to show our experience of 13 years in 134 patients with our technique of orbicularis oculi myectomy. Methods: From September 2000 to July 2013, we operated on 134 patients with an age range of 28–77 years. Of these patients, 104 had myectomies via lifting and 22 via a blepharoplasty approach. Five patients had myectomies for treatment of blepharospasm and a further three patients to restore symmetry in facial palsy. An evaluation of the results was performed by two medical students. Results: Our results showed reduction of the wrinkles in all cases. For the statistical analysis the Wilcoxon test was performed. The p value was less than 0.001 showing a significant reduction of crows’ feet wrinkles in both sides when the orbicularis myectomy was performed, via blepharoplasty or lifting. For myectomy performed for blepharospasm or facial palsy, the statistical analysis was not done due to the low numbers. Conclusion: In the appropriate patient, orbicularis oculi myectomy is an effective and long-term treatment for crows’ feet wrinkles with a low risk of complications and high patient satisfaction. Level of Evidence IV: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266.
Keywords: Botulinum toxin; Crows’ feet wrinkles; Myectomy; Orbicularis oculi